Efectos De La Fertilización Nitrogenada Y Fosfatada Sobre Poblaciones De Micorrizas Asociadas Al Cultivo De Cacao - Coello, Wilson Latacela; Navarrete, Eduardo Colina; Arteaga, Carlos Castro; Aragone, Danilo Santana; Paredes, Joffre León; Vásquez, Guillermo García; Cabezas, Miguel Goyes; Suarez, Maribel Vera (European Scientific Journal, ESJ, 2017)
Cocoa is one of the most significant assets in the ecuadorian agricultural structure, which also provides a good source of income for thousands of farmworker families. However, fertilization research works in cocoa cultivation have been relatively scarce. Decades of global research have shown that mycorrhizal fungi determine the fertilization and conservation of agrosystems. Fertilization is considered to be among the cultural and agricultural practices affecting mycorrhizas, which diminishes or prevents the fungal colonization. The objectives of research works were the following: the characterization of mycorrhiza species associated with cocoa, to determine the effects of nitrogen and phosphate fertilization in plant population and to identify the critical dose affecting the fungus development. A factorial design was used (AxBxC), with two (2) application systems, four (4) doses of nitrogen fertilizer, and two (2) doses of phosphate fertilizer with three repetitions. The turkey’s test was used to evaluate means with confidence interval of 95%. The evaluated variables were: diameter and length of cocoa pods, number of cocoa pods per tree, index of cocoa beans and almond yield per hectare, as well as, mycorrhizal spore counting, percentage of mycorrhizal fungi colonization, visual density of endophyte, and characterization of mycorrhiza species. The results concluded that the application of 100 Kg/ha N + 70 kg/ha P in the system below the soil surface, achieved yield increments of 68% over the absolute witness. The same dose and application method, increased the number of spores per gram of soil, mycelium colonization and density of mycorrhizal endophyte in roots.